Characteristics of the semantic content of the concept of "game giftedness" (using the example of football) - Rizvanova A. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study - to scientifically substantiate the essence and content of the concept of "gaming talent" in sports activities.